2014
DOI: 10.25011/cim.v37i2.21093
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-based measures of sedentary behavior and cardio-metabolic risk in active older adults

Abstract: Accelerometer-based measures of sedentary behavior and cardiometabolic risk in active older adults Abstract Purpose: Sedentary behavior has been proposed as an independent cardio-metabolic risk factor even in adults who are physically active through recreational activity. Because little is known about the metabolic e ects of sedentariness in seniors, the relationship between sedentary behavior and cardio-metabolic risk was examined in physically active older adults.Methods: Fi y-four community dwelling men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
0
20
0
1
Order By: Relevance
“…We hypothesized that greater amounts of sedentary behavior would be associated with higher systolic BP (SBP), diastolic BP (DBP), and mean arterial pressure (MAP) in patients with MS based on the frequencies of sedentary behavior and hypertension in patients with MS 4 and the relationship between hypertension and sedentary behavior in the general population. [15][16][17][18] We further hypothesized that the association would be stronger in persons with MS compared with controls considering the possible role of a chronic disease condition.…”
Section: Possible Covariates Of Sitting Time and Hypertensionmentioning
confidence: 99%
“…We hypothesized that greater amounts of sedentary behavior would be associated with higher systolic BP (SBP), diastolic BP (DBP), and mean arterial pressure (MAP) in patients with MS based on the frequencies of sedentary behavior and hypertension in patients with MS 4 and the relationship between hypertension and sedentary behavior in the general population. [15][16][17][18] We further hypothesized that the association would be stronger in persons with MS compared with controls considering the possible role of a chronic disease condition.…”
Section: Possible Covariates Of Sitting Time and Hypertensionmentioning
confidence: 99%
“…All studies were observational—four were cross-sectional [2326], four were prospective longitudinal [15, 2729], one was retrospective longitudinal [30••], and one was a cross-sectional analysis of baseline data from an intervention study [31••]. All studies were published from 2007 to 2015.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were published from 2007 to 2015. Sample sizes (either full sample or portion of sample ≥60 years) ranged from 54 [23] to 62,954 [28]. By design, all studies in this review included samples exclusively age ≥60 [2327,30••, 31••] or reported on older subgroups [15, 28, 29], but studies varied in age limits—four studies reported on participants ≥60 [24, 26, 28, 29], three studies on participants ≥65 [23, 25, 27], two studies on participants ≥70 [15, 31••], and one study on participants age ≥73 [30••].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations